Preparation of novel two-stage structure MnO micrometer particles as lithium-ion battery anode materials. Issue 50 (10th August 2018) - Pei, Xian-Yinan; Mo, Dong-Chuan; Lyu, Shu-Shen; Zhang, Jian-Hui; Fu, Yuan-Xiang
Abstract : MnO micrometer particles with a two-stage structure (composed of mass nanoparticles) were produced via a one-step hydrothermal method using histidine and potassium permanganate (KMnO4 ) as reagents, with subsequent calcination in a nitrogen (N2 ) atmosphere. Abstract : MnO micrometer particles with a two-stage structure (composed of mass nanoparticles) were produced via a one-step hydrothermal method using histidine and potassium permanganate (KMnO4 ) as reagents, with subsequent calcination in a nitrogen (N2 ) atmosphere. When the MnO micrometer particles were utilized in lithium-ion batteries (LIBs) as anode materials, the electrode showed a high reversible specific capacity of 747 mA h g −1 at 100 mA g −1 after 100 cycles, meanwhile, the electrode presented excellent rate capability at various current densities from 100 to 2000 mA g −1 (∼203 mA h g −1 at 2000 mA g −1 ). This study developed a new approach to prepare two-stage structure micrometer MnO particles and the sample can be a promising anode material for lithium-ion batteries.